The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1080/15487733.2013.11908115
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability and meat consumption: is reduction realistic?

Abstract: Meat is critical with respect to sustainability because meat products are among the most energy-intensive and ecologically burdensome foods. Empirical studies of the meat-consumption frequency of Dutch consumers show that, apart from meat-avoiders and meat-eaters, many people are meat-reducers that eat no meat at least one day per week. Meat-consumption frequencies provide empirical evidence for different modes of "flexitarianism," including light, medium, and heavy flexitarians. In particular, the existence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
129
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(144 citation statements)
references
References 43 publications
1
129
0
2
Order By: Relevance
“…Such a cultural change would be much harder to achieve, but is required to adopt new sustainable and healthy dietary patterns. Maintaining existing dietary patterns may not be enough to reach the true potential of dietary change (Dagevos and Voordouw 2013;Gonzalez Fischer and Garnett 2016;Green et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Such a cultural change would be much harder to achieve, but is required to adopt new sustainable and healthy dietary patterns. Maintaining existing dietary patterns may not be enough to reach the true potential of dietary change (Dagevos and Voordouw 2013;Gonzalez Fischer and Garnett 2016;Green et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…as a result of rearing, transportation and slaughtering practices) may lead to the voluntary avoidance of some or even all animal products in one's diet (e.g. Beardsworth and Bryman 2004;Beardsworth and Keil 1991;Dagevos and Voordouw 2013;Dibb and Fitzpatrick 2014;Graça et al 2015;Santos and Booth 1996) and are increasingly integrated into the commercial food system (Beardsworth and Keil 1991). This has been confirmed by Mäkiniemi et al (2011), who investigated differences between ethical and unethical food on the basis of their observation that there has been a substantial growth in ethical food consumption.…”
Section: Knowledge and Skillsmentioning
confidence: 97%
“…Several authors found that habits and routines are among the main barriers to reduced meat consumption (Lea et al 2006;Dagevos and Voordouw 2013;Graça et al 2015). Dibb and Fitzpatrick (2014) add that many of our day-today food habits are routine in that we eat often and without much deliberation.…”
Section: Habits and Tastementioning
confidence: 99%
See 1 more Smart Citation
“…Our subject pool is a representative sample of the population of non-vegetarian households in the Netherlands because: (i) we started with a representative sample of Dutch households; (ii) we mentioned neither the topic nor the purpose of our study in our contacts with the respondents in the selection phase of the study; and (iii) 93% of the households who were invited for the initial survey, ended up participating in the experiment. For a general analysis of meat consumption in the Netherlands, see Gilsing et al [45] and also Dagevos and Voordouw [46]. Respondents were asked whether they were willing to participate in a study, and, if so, whether they were available during the entire period in which the study was implemented, whether they ate meat, and who was responsible for the household's groceries shopping.…”
Section: A Field Experimentsmentioning
confidence: 99%